The Roles of Theta absorption, Argument Fusion and Argument Structure Theory in Translating Arabic Religious Verbs - Alshehri, Awad H.; Jalabneh, Atef (Forum for Linguistic Studies, 2025)
The objective: this article explores the new version translation of Arabic religious verbs, namely, ?ic tamara ‘travelled’, hajja ‘travelled’, sabbaha ‘sanctified’, ?asra ‘ordered’, salla ‘granted, asked’, saama ‘fasted’, zakka ‘gave’, ?itaqa ‘feared’ and ?aamana ‘believed’. It was difficult for translators of the Holy Quran and others in the recent relevant literature to give satisfactory meanings for the verbs to convince the reader. As these verbs have remote argument religious contents which were not covered in the literature, they were given the correct English equivalents to uncover the religious contents. Methodology: the researchers used qualitative and theoretical approaches to discuss data gathered from Holy Quran and written books in modern Arabic syntax. Therefore, the researchers referred to Theta Absorption Mechanism, Argument Fusion and Argument Structure Theory to analyze the data. Conclusions, the researchers proved that there are intransitives verbs that have several fused syntactic constituents, which are overt at D-structure but must be translated at the logical form. They carry specific theta roles that constitute the syntactic structure and meaning of the verbs which lead to correct religious translation at the logical form (LF). However, there are certain religious transitive verbs that posit their essential arguments at D-structure, but they can absorb them as the arguments carry semantic connotations in translation at LF; Also, there is another category of transitive verbs that cannot absorb the internal arguments, and all of them must be translated; thus, whether the verb is intransitive or transitive, fused theta roles constitute the religious contexts.